A visit to Krossrgil, North-central Iceland 1954, with special reference to the Pink-footed Goose - Yeates, G K (Wildfowl, 1954)
In June 1954, in company with Lt-Col Niall Rankin, I visited North Iceland in order to see and photograph the Pink-footed Goose (Anser brachyrhynchus) Our real reason for concentrating on the Pinkfoot was, of course, that we both wanted to do so, even if the whole world had done so before us. It was certainly a bird which had never been really adequately photographed at the nest. There were, however, other equally serious considerations. No ornithologist seems to have studied the Pinkfoot for very long in the incubation period; and the colonies in North-Central Iceland have been rarely visited.